Role of Echocardiography In Acute Rheumatic Fever Compared With Jones Criteria - Manuj Kumar Sarkar; Kamal Malviya; Amit Singh Barpha; Arati Lalchandani; Subhra Dey (International Journal of Medical Research and Review, 2015)
Introduction: Rheumatic heart disease (RHD), the sequel of acute rheumatic fever (ARF), is a very common cause of cardiovascular mortality and morbidity. RHD results in enormous disease burden translating into huge economic and social losses in India. Classical ARF is still encountered across the country. The diagnosis of RF remains clinical. Echocardiography is a very important diagnostic tool to detect valvular lesions in patients with carditis of acute rheumatic fever. Jones criteria has been modified several times but the role of echocardiography in detecting carditis is not been mentioned in any modifications.Methods and Material: The study was conducted from November 2007 to October 2009, for duration of 2 years in GSVM medical college, Kanpur. Patients with joint pain (arthritis, arthralgia), chest pain, dyspnoea, palpitation, chorea (involuntary movements), subcutaneous nodule, erhythema marginatum, sore throat, skin infection, recurrent upper respiratory tract infection etc, who visited OPD, health camps, or were admitted in Medicine and Pediatrics department were included in the study. Thus selected patients were undergone detailed history taking, clinical examinations particularly they were evaluated to find out whether they were having symptom/signs of carditis and fulfilling Jones criteria to diagnose Acute Rheumatic fever. The same patients were evaluated with Echocardiography to detect carditis.Results: 40 patients were diagnosed as acute rheumatic fever based on revised Jones criteria. Only 24 patients showed carditis clinically, but Echocardiography showed 27 patients with evidence of carditis. Ventricular septal defect was also detected in 3 patients, which was wrongly detected as carditis in clinical examination. 21 patients had carditis clinically, but echocardiography diagnosed carditis in 27 patients. (p value <0.05).Conclusion: Echocardiography plays a very important role in detection of carditis. Echocardiographic confirmation of carditis could be accepted as major criteria.